Perlindungan Hukum bagi Isteri yang Ditelantarkan oleh Suami Ditinjau dari Perspektif Hukum Perdata - Rohman , Roni Saepul; Taun, Taun (Fakultas Hukum Universitas PGRI Kanjuruhan Malang, 2021)
Husbands have absolute rights and obligations in building a household. Vice versa, a wife has the same absolute rights and obligations in managing the household. There are still husbands or wifes who are negligent in carrying out their obligations and even do not carry them out. The Method used in this research is the normative legal research method,which is a study that examines a document, namely various secondary data such as statutory regulations, legal theory, court decisions and legal scholar opinions. The case that often occurs is neglect by husbands against theirs own wifes. There are many factors that cause a husband to abandon his wife and even his own family. However, a wife has the right to sue the husband in court by filing a claim for livelihood, which is a legal remedy that the wife can take to get justice.